Norfluoxetine is the only metabolite of fluoxetine in zebrafish (Danio rerio) embryos that accumulates at environmentally relevant exposure scenarios - Zindler, Florian; Tisler, Selina; Lörracher, Ann-Kathrin; Zwiener, Christian; Braunbeck, Thomas (Environmental science & technology, 2020)
Fluoxetine has been recognized as one of the most toxic pharmaceuticals in the aquatic environment. Since there is growing evidence that the toxic potential of fluoxetine in surface waters is markedly influenced by its own metabolism in aquatic species, this study investigated the biotransformation of fluoxetine in the zebrafish embryo - an aquatic model organism of intermediate complexity. Zebrafish embryos were exposed to 0.1, 1.0, 10, 50, and 5000 μg/L of fluoxetine from 48 to 120 h post-fertilization (hpf), and the accumulation of fluoxetine and its metabolites was analyzed over time. Additionally, depuration of fluoxetine and its metabolites from 96 to 120 hpf was investigated, and autoinhibitory effects of fluoxetine on phase I biotransformation were analyzed. Exposure to 5000 μg/L fluoxetine resulted in elevated 7-ethoxyresorufin-O-deethylase (EROD) activity of cytochrome P450 enzymes and continuous accumulation of fluoxetine and 11 fluoxetine metabolites. Embryos exposed to 10 and 50 μg/L fluoxetine were able to reduce fluoxetine accumulation from 94 to 120 hpf. During depuration, accumulation of fluoxetine and most metabolites was clearly reduced, and biotransformation shifted in favor of norfluoxetine, the primary fluoxetine metabolite in humans. Findings demonstrated that norfluoxetine is the only metabolite of fluoxetine that accumulates in zebrafish embryos at environmentally relevant exposure scenarios.